De la historia de la filosofía a la filosofía de la filosofía de José Gaos (1900-1969) - Mario Magallón Anaya (Ksiegarnia Akademicka Publishing, 2021)
About the History of Philosophy in Philosophy of Jose Gaos’ Philosophy